Social determinants are crucial factors in the long-term prognosis of severely decompensated acute heart failure in patients over 75 years of age. Issue 2 (August 2018) - Matsushita, Masato; Shirakabe, Akihiro; Hata, Noritake; Kobayashi, Nobuaki; Okazaki, Hirotake; Shibata, Yusaku; Nishigoori, Suguru; Uchiyama, Saori; Kiuchi, Kazutaka; Asai, Kuniya; Shimizu, Wataru
Highlights: Nine-hundred fifteen patients with acute heart failure including 442 patients ≥75 years were enrolled. Socially vulnerable fulfilled one of the marital, children, and living criteria. Socially vulnerable had significantly poorer mortality in all and elderly cohort. Socially vulnerable was an independent predictor of mortality in the elderly cohort. Organization of the social structure might improve their prognosis. Abstract: Background: The association between social factors and the long-term prognosis of acute heart failure (AHF) remains unclear. Methods and results: One thousand fifty-one AHF patients were screened, and 915 were enrolled. Four hundred forty-two AHF patients ≥75 years of age (the elderly cohort) were also included in a sub-analysis. Participants who fulfilled one of the three marital status-, offspring-, and living status-related criteria were considered socially vulnerable. On this basis they were classified into the socially vulnerable ( n = 396) and non-socially vulnerable ( n = 519) groups in the overall cohort, and the socially vulnerable ( n = 219) and non-socially vulnerable ( n = 223) groups in the elderly cohort. Kaplan–Meier curves showed that the survival rate of the socially vulnerable group was significantly poorer than that of the non-socially vulnerable group in the overall ( p = 0.049) and elderly ( p = 0.004) cohorts. A multivariate Cox regression model revealed that social vulnerability was an independent predictor of 1000-day mortality in the overall [hazard ratio (HR): 1.340, 95% confidence interval (CI): 1.003–1.043, p = 0.048] and elderly cohort (HR: 1.531, 95% CI: 1.027–2.280, p = 0.036). Regarding the components of social vulnerability, the marital status was an independent factor in the elderly cohort (HR: 1.500, 95% CI 1.043–2.157, p = 0.029). Conclusion: Social vulnerability was independently associated with long-term outcomes in AHF patients, especially in the elderly cohort. Organization of the social structure of AHF patients might be able to improve their prognosis.